Fluid Overload and Kidney Injury Score as a Predictor for Ventilator-Associated Events - Jarin Vaewpanich; Jarin Vaewpanich; Jarin Vaewpanich; Ayse Akcan-Arikan; Ayse Akcan-Arikan; Ayse Akcan-Arikan; Jorge A. Coss-Bu; Jorge A. Coss-Bu; Curtis E. Kennedy; Curtis E. Kennedy; Jeffrey R. Starke; Jeffrey R. Starke; et al. (Frontiers Media S.A., 2019)
Objective: The Pediatric and Neonatal Working group developed new ventilator associated events (VAE) definitions for children and neonates. VAE includes ventilator-associated condition (VAC), infection-related ventilator-associated complication (IVAC), and ventilator-associated pneumonia (VAP). Acute kidney injury (AKI) and fluid overload (FO) have been associated with worse clinical outcomes of ventilated children. Fluid Overload and Kidney Injury Score (FOKIS) is an automatically calculated score that combines AKI and FO in one numeric quantifiable metric. This study analyzed the association between FOKIS and VAE.Design: Retrospective matched case control study.Setting: A freestanding children's hospital.Patients: A total of 168 who were ventilated > 2 days.Interventions: None.Measurements and Main Results: We identified 42 VAC cases (18 IVAC and 24 non-infection-related VAC cases). Controls were matched to cases for age, immunocompromised status and ventilator days prior to VAC. VAC cases had longer ICU days, median (IQR), 28.5 (15, 47) vs. controls 11 (6, 16), p < 0.001; longer ventilation days, 19.5 (13, 32) vs. 9 (4,13), p < 0.001; and higher hospital mortality, 45.2 vs. 18%, p < 0.001. VACs had a higher incidence of AKI, 85.7 vs. 47.3%, p < 0.001; higher peak daily FO% within 3 days preceding VAC, mean (SD), 8.1(7.8) vs. 4.1 (3.4), p < 0.005; and higher peak FOKIS, 6.4(3.8) vs. 3.7(2.8), (p < 0.001). Multivariate regression model adjusted for severity of illness identified peak FOKIS (odds ratio [OR] 1.29, 95%CI: 1.14-1.48, p < 0.001) and peak inspiratory pressure (OR 1.08, 95%CI: 1.02-1.15, p = 0.007) as risk factors for VAC.Conclusions: The FOKIS and its clinical variables were associated risk factors for ventilator-associated events. Further studies will determine the utility of FOKIS as a predictor for VAEs.